RELIGIUSITAS, DUKUNGAN SOSIAL, STRES, DAN PENYESUAIAN WANITA BERCERAI - Muhammad, Larastyan Yang Bogaan; Muflikhati, Istiqlaliyah; Simanjuntak, Megawati (Jurnal Ilmu Keluarga dan Konsumen, 2019)
Divorce rates in Indonesia are increasing annually and caused by many factors such as infidelity, economics factor, and domestic violence. Divorce has an impact on many aspects of a woman’s life including physical health, mental health, financial status, child custody, education, and social status. This study aimed to analyze the effect of religiosity, social support, and stress on the adjustment of divorced women. The samples were chosen by purposive technique sampling with the criteria of women who have divorced between 1 and 12 months and the numbers of samples are 100 divorced women. The research location was chosen purposively, in the city of Tangerang, West Java Province. The results showed religiosity, stress, and adjustment as a moderate category but low categorized social support. The divorced women in this study were in early adulthood who more than half of them are high school graduated and working in the private sector. Infidelity is the main cause of divorce with a divorce period of three months after the decision and divorce are understood by women as plaintiffs. The results revealed that high categorized religiosity (trust, commitment, and religious behavior) of divorced women have a significant positive effect on the adjustment of divorced women. Religiosity has a significant negative effect on the level of stress, which means that if religiosity is high then the stress level in divorced women will below, and vice versa. Stress levels have a significant negative effect on the adjustment of divorced women, which means that if the stress level of divorced women is high then the adjustment of divorced women will below, and vice versa. In this study, social support did not affect the adjustment of divorced women.